(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the issues of improving the methodology for developing independent work skills of academic lyceum students. The pedagogical and psychological essence of independent work skills, their role in the educational process and their importance in increasing the cognitive activity of students are highlighted. The ways of developing independent work skills based on the use of modern pedagogical technologies, interactive methods and information and communication tools are analyzed.